Characterizing Granuloma Annulare in 73 Pediatric Patients - Ania Stolarczyk; Fatima Bawany; Simon Hernandez; Glynis A. Scott; Maria R. Cordisco (Hindawi Limited, 2023)
Background. Granuloma annulare (GA) is a common, benign, idiopathic inflammatory dermatosis. Aside from case reports and small studies, there are limited data about the characteristics of GA in children. Objective. This study aimed to better characterize the epidemiologic and clinical features, triggering factors, disease associations, and outcomes of GA in the pediatric population. Methods. We conducted a retrospective study of 73 pediatric patients diagnosed with GA at the University of Rochester Medical Center over a 7-year period. Results. The most common subtype was localized GA (71.2%, n = 52), followed by subcutaneous (also known as "deep GA"; 16.4%, n = 12) and generalized (12.3%, n = 9) subtypes. Over 90% of patients had idiopathic GA, with the remaining patients reporting viral infection or trauma as triggers. Half of the patients studied had comorbid conditions, most frequently atopic dermatitis (17.8%, n = 13), obesity (9.59%, n = 7), asthma (6.85%, n = 5), and allergic rhinitis (6.85%, n = 5). The median duration of the disease was 11.00 months (interquartile range (IQR) 15.75 months); generalized GA had the shortest duration (median 10.00 months, IQR 15.50 months), while subcutaneous GA had the longest duration (median 12.00 months and IQR 29.00 months). Although recurrence rates for subcutaneous and generalized GA were high at 45.5% and 33.3%, respectively, most patients achieved clearance or improvement with treatment. Conclusion. Most cases of GA in our study were idiopathic, with no clear differences between GA subtypes and associated comorbidities. Topical steroids were the most prescribed treatment with mixed efficacy.